Determinants of early antenatal care booking among pregnant mothers attending antenatal care at public health facilities in the Nole Kaba district, western Ethiopia: unmatched case–control study - Firaol Regea Gelassa; Segni Mulugeta Tafasa; Diriba Kumera (BMJ Open, 2023)
Background Early initiation of antenatal care (ANC) is vital for the early detection and treatment of adverse pregnancy outcomes. Despite the widespread convenience of free ANC services, most women in Ethiopia attend their initial antenatal clinic late and fail to come back for follow-up care, which results in both maternal and fetal complications. Despite the fact that assessing the determinants of early ANC booking based on the local context is advised, it is not well studied in the study area.Objective This study aimed to assess determinants of early ANC booking among pregnant women attending ANC at public health facilities in the Nole Kaba district, western Ethiopia.Methods Facility-based unmatched case–control study design was conducted from April to June 2020. Systematic random sampling was used to select a total of 297 participants. A validated, pretested and structured instrument was used to interview the participants. The data were cleaned and coded before being entered into Epi-Info V.7.2.2.6 and exported to SPSS V.25 for analysis. The logistic regression analyses were done to assess the determinants of early ANC booking. Adjusted odds ratio (AOR) with 95% CI was estimated to measure the strength of the association. The level of statistical significance was set at a p value <0.05.Result A total of 297 pregnant women participated in the study (99 cases and 198 controls), with a 100% response rate. Place of residence (AOR=2.21, 95% CI 1.11, 2.72), level of education (AOR=3.42, 95% CI 1.01, 6.04), planned pregnancy (AOR=8.01, 95% CI 2.79, 23.03), history of abortion (AOR=5.96, 95% CI 2.07, 17.13), places of previous delivery (AOR=4.57, 95% CI 1.09, 19.12), presence of accompanied by husband during ANC visit (AOR=2.48, 95% CI 2.77, 7.98) and media exposure (AOR=6.95, 95 CI 2.68, 18.02) were found statistically significant.Conclusion and recommendations Places of residence, educational level, pregnancy, having a history of abortion, accompanied by the husband during ANC visit, place of previous delivery and media exposure were significantly associated with early initiation of ANC. Therefore, health extension programmes on early ANC initiation should be strengthened by giving priority to less educated women and living in rural areas.